1994
DOI: 10.1017/s0950268800051475
|View full text |Cite
|
Sign up to set email alerts
|

Clonal dissemination of two MRSA strains in Germany

Abstract: SUMMARYClonal dissemination of two different MRSA strains, both clumping factor negative, has been observed in Germany for more than a year. Both strains possess the mec-A determinant and each exhibits a characteristic genomic DNA fragment pattern. One strain has spread in the north, the other in the south-west of Germany.Intensive care units are mainly affected by MRSA-infections and probably play a special role in further intra-and inter-hospital spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Since then, investigators in many other countries have reported the occurrence of the predominant spread of 1 strain in a defined geographic area (Germany [27,28], Poland [16], Turkey [29], Portugal and Spain [18,30,31], Holland [32], and Australia [33]). …”
Section: Discussionmentioning
confidence: 99%
“…Since then, investigators in many other countries have reported the occurrence of the predominant spread of 1 strain in a defined geographic area (Germany [27,28], Poland [16], Turkey [29], Portugal and Spain [18,30,31], Holland [32], and Australia [33]). …”
Section: Discussionmentioning
confidence: 99%
“…The introduction of SmaI macrorestriction patterns at the beginning of the 1990s led to identification of epidemic strains at national and international level (Witte et al, 1994Criso´stomo et al, 2001).…”
Section: Understanding Evolution Emergence and Spread Of Mrsa By Molmentioning
confidence: 99%
“…As test organisms for antimicrobial activity assays we used the Gram-negative bacteria Escherichia coli ATCC 25922, E. coli DC2 (antibiotic-susceptible penetration mutant), [37] Pseudomonas aeruginosa ATCC 9027, P. aeruginosa K799/61 (antibiotic-susceptible penetration mutant), [38] Burkholderia cepacia DSM 7288 (resistant to cationic peptides), [39] B. vietnamiensis DSM 11319, B. multivorans BF7 (clinical isolate obtained from Prof. Dr. A. Bauernfeind, MICOER-Institute, Munich, Germany) and the Gram-positive bacteria Staphylococcus aureus SG511, S. aureus 134/ 93 (MRSA), [40] Bacillus subtilis ATCC 6633, Micrococcus luteus ATCC 10240 and ATCC 9341, Mycobacterium vaccae IMET 10670, and Mycobacterium fortuitum B.…”
Section: Antimicrobial Inhibition Assaysmentioning
confidence: 99%